Higher Dimensional Spherically Symmetric String Cosmological Model with Zero Mass Scalar Field in Lyra Geometry - Pawar, K. N.; Netnaskar, M. D. (Journal of Scientific Research, 2025)
In this article, A higher-dimensional string cosmological model with a zero-mass scalar field in Lyra’s geometry has been investigated by considering a five-dimensional spherically symmetric space-time. To obtain the deterministic solutions for field equations, some physically plausible conditions are taken into account. The relation between the metric coefficients was assumed to be B= nA, and due to the highly non-linear nature of the field equations, the case γ = ρ was considered. Furthermore, calculations were performed for various physical and kinematical parameters, and their astrophysical implications were analyzed, revealing a strong resemblance to recent observational data.